2016
DOI: 10.1108/jgm-09-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

A practical perspective on repatriate knowledge transfer

Abstract: Purpose – The purpose of this paper is to identify organizational support practices that facilitate repatriate knowledge transfer (RKT) in order to overcome the lack of strategic utilization of repatriate knowledge. Design/methodology/approach – In Study 1, 134 repatriates responded to an online questionnaire and evaluated the organizational support that their organizations provided to facilitate RKT. In Study 2, 22 repatriates and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In this study, it was found that POS has significant positive direct effect on PJP, the finding is consistent with past empirical findings of Na-Nan, Saribut and Sanamthong [9], Xiu, Dauner and McIntosh [10], Du et al [11], Byrne and Hochwarter [12], Biswakarma [13], Burmeister and Deller [14], Yaakobi and Weisberg [15], Wickramasinghe and Wickramasinghe [8], Hakkak, Gashti, and Nawaser [1], Guan, Sun, Hou, Zhao, and Luan [17], Armeli, Eisenberger, Fasolo, and Lynch [16], Eisenberger, Huntington, and Hutchison [6], where it was mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization [13]. Burmeister and Deller [14], Yaakobi and Weisberg [15] concluded that perceived environmental support and knowledge sharing as the main factors which can heightened active job performance. However, it fails to support the study which advocate that there is no relationship between POS and PJP e.g., Bennett and Liden [18] and Wayne, Shore, and Liden [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, it was found that POS has significant positive direct effect on PJP, the finding is consistent with past empirical findings of Na-Nan, Saribut and Sanamthong [9], Xiu, Dauner and McIntosh [10], Du et al [11], Byrne and Hochwarter [12], Biswakarma [13], Burmeister and Deller [14], Yaakobi and Weisberg [15], Wickramasinghe and Wickramasinghe [8], Hakkak, Gashti, and Nawaser [1], Guan, Sun, Hou, Zhao, and Luan [17], Armeli, Eisenberger, Fasolo, and Lynch [16], Eisenberger, Huntington, and Hutchison [6], where it was mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization [13]. Burmeister and Deller [14], Yaakobi and Weisberg [15] concluded that perceived environmental support and knowledge sharing as the main factors which can heightened active job performance. However, it fails to support the study which advocate that there is no relationship between POS and PJP e.g., Bennett and Liden [18] and Wayne, Shore, and Liden [19].…”
Section: Discussionsupporting
confidence: 92%
“…Biswakarma [13] found a significant relationship between perceived job performance and perceived organizational support, and mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization. Likewise, the studies of Burmeister and Deller [14], Yaakobi and Weisberg [15] proposed perceived environmental support and knowledge sharing as the main factors which enhanced effective employee job performance. Armeli, Eisenberger, Fasolo, and Lynch [16] studied patrol officers in USA with high socio-emotional needs, found that there was generally a positive relationship between Perceived Organizational Support and performance.…”
Section: Perceived Organizational Support and Perceived Job Performancementioning
confidence: 99%
“…In this regard, practitioners should especially acknowledge that the findings from both academic research and practitioner-oriented reports have frequently observed the lack of availability of repatriation support practices in MNCs (e.g. Burmeister and Deller, 2016; Brookfield Global Relocation Services, 2016; Pattie et al. , 2010; Tahir, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, practitioners should especially acknowledge that the findings from both academic research and practitioner-oriented reports have frequently observed the lack of availability of repatriation support practices in MNCs (e.g. Burmeister and Deller, 2016;Brookfield Global Relocation Services, 2016;Pattie et al, 2010;Tahir, 2018). For instance, a large practitioner-oriented report that consisted of 124 large MNCs around the world, the 2016 Talent Mobility Trends Survey (Brookfield Global Relocation Services, 2016) found that 44% of the participated MNCs did not have any initiatives or programs in place to increase repatriate retention upon return.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Moreover, inpatriates could also value the experience and relationships developed at the HQ to transfer local knowledge to HQ. But this advantage is constrained by the existence of certain conditions at the organizational level that fosters the repatriate knowledge transfer (Burmeister and Deller, 2016).…”
Section: International Assignments and Multinational Companies Performancementioning
confidence: 99%